Changes in the cuticular profile but not aggression of termites along a tropical elevation gradient - Camarota, Flávio; Viana‐Junior, Arleu B.; Vidal, Diogo M.; Zarbin, Paulo H. G.; Neves, Frederico S. (Ecological entomology, 2025)
Communication is critical for social insects and largely mediated by cuticular hydrocarbon compounds (CHCs). The CHCs are diverse and involved in different functions, including nestmate recognition, and protection against desiccation. Their production is costly and context‐dependent, and organisms must prioritise those necessary for survival and fitness in a given habitat. While environmental and abiotic factors are key determinants of the CHCs' profile, we still know little about the effects of elevation in CHC composition in tropical mountain social insects. We investigated the role of elevation on the abundance and composition of CHCs in the termite species Nasutitermes coxipoensis, a widespread termite species in Brazil. We studied the populations of N. coxipoensis in the largest Brazilian mountain range. Besides assessing the differences in CHC composition, we conducted behavioural assays to test the recognition ability of different colonies within the elevational gradient. We found an effect of elevation in the chemical profile of CHCs in N. coxipoensis, with an increased abundance of n‐alkanes and dimethyl‐alkanes with increasing elevation. When evaluating the effect of elevation on the dissimilarity of CHC compounds, we observed that n‐alkanes and dimethyl alkanes were affected differently, but in general, compounds increased their dissimilarity with elevational distance. Finally, changes in CHC profiles did not affect aggression between neighbouring colonies along the elevation gradient. Our results indicate that environmental factors play a limited role in shaping termite chemical profiles along a tropical elevation gradient, with no influence on aggression between neighbouring colonies from distinct elevations. We found an effect of elevation in the chemical profile of CHCs in N. coxipoensis, with an increased abundance of n‐alkanes and dimethyl alkanes with increasing elevation. While n‐alkanes and dimethyl alkanes were affected differently, compounds increased their dissimilarity with elevational distance. The observed changes in CHC profiles did not affect aggression between neighbouring colonies along the elevation gradient.